An Integrative Study of the Genetic, Social and Environmental Determinants of Chronic Kidney Disease Characterized by Tubulointerstitial Damages in the North Central Region of Sri Lanka. Issue 1 (17th April 2014) - Nanayakkara, Shanika; Senevirathna, STMLD; Abeysekera, Tilak; Chandrajith, Rohana; Ratnatunga, Neelakanthi; Gunarathne, EDL; Yan, Junxia; Hitomi, Toshiaki; Muso, Eri; Komiya, Toshiyuki; Harada, Kouji H.; Liu, Wanyang; et al.
Abstract : An Integrative Study of the Genetic, Social and Environmental Determinants of Chronic Kidney Disease Characterized by Tubulointerstitial Damages in the North Central Region of Sri Lanka: Shanika NANAYAKKARA, et al. Department of Health and Environmental Sciences, Graduate School of Medicine, Kyoto University— Objectives: Previous investigations on chronic kidney disease of unknown etiology characterized by tubulointerstitial damages (CKDu) in the North Central Region (NCR) of Sri Lanka have supported the involvement of social, environmental and genetic factors in its pathogenesis. Methods: We conducted a social‐environmental‐ and‐genetic epidemiology study on a male population in NCR to investigate the genetic and environmental contributors. We recruited 311 case‐series patients and 504 control candidates. Of the 504 control candidates, 218 (43%) were eliminated because of the presence of hypertension, proteinuria, high HbA1c, high serum creatinine or high alpha‐1 microglobulin in urine. Results and Discussion: None of 18 metals measured (μg/l) in urine, including Cd, As and Pb, showed significantly higher concentrations in cases compared with controls. As speciation results showed that 75.80% of total urinary As was in the form of arsenobetaine, which is non‐toxic to humans. None of the metal concentrations in drinking water samples exceeded guideline values. A genome‐wide association study (GWAS) was conducted to determine the genetic contributors. The GWAS yielded a genome‐wide significant association with CKDu for a single nucleotide polymorphism (SNP; rs6066043; p=5.23 ~ 10.9 in quantitative trait locus analysis; p=3.73 ~ 10.8 in dichotomous analysis) in SLC13A3 (sodium‐dependent dicarboxylate transporter member 3). The population attributable fraction and odds ratio for this SNP were 50% and 2.13. Genetic susceptibility was identified as the major risk factor for CKDu. However, 43% of the apparently healthy male population suffers from non‐communicable diseases, suggesting their possible influence on CKDu progression.